Mammalian antiviral systems directed by small RNA. - Tomoko Takahashi; Steven M Heaton; Nicholas F Parrish (PLoS Pathogens)
There are strong incentives for human populations to develop antiviral systems. Similarly, genomes that encode antiviral systems have had strong selective advantages. Protein-guided immune systems, which have been well studied in mammals, are necessary for survival in our virus-laden environments. Small RNA-directed antiviral immune systems suppress invasion of cells by non-self genetic material via complementary base pairing with target sequences. These RNA silencing-dependent systems operate in diverse organisms. In mammals, there is strong evidence that microRNAs (miRNAs) regulate endogenous genes important for antiviral immunity, and emerging evidence that virus-derived nucleic acids can be directly targeted by small interfering RNAs (siRNAs), PIWI-interacting RNAs (piRNAs), and transfer RNAs (tRNAs) for protection in some contexts. In this review, we summarize current knowledge of the antiviral functions of each of these small RNA types and consider their conceptual and mechanistic overlap with innate and adaptive protein-guided immunity, including mammalian antiviral cytokines, as well as the prokaryotic RNA-guided immune system, CRISPR. In light of recent successes in delivery of RNA for antiviral purposes, most notably for vaccination, we discuss the potential for development of small noncoding RNA-directed antiviral therapeutics and prophylactics.